Successive negative contrast in a bird: starlings' behaviour after unpredictable negative changes in food quality - Freidin, Esteban (2009)
In a successive negative contrast (SNC) procedure, subjects used to a familiar contingency are unexpectedly shifted to a less favourable one. Typically, mammals in the new condition show lower anticipatory and consummatory responses than controls that only experience the low contingency, but similar experiments in birds have failed to show SNC. We investigated SNC in European starlings, Sturnus vulgaris. In experiment 1, birds that were shifted from mealworms (preferred food) to turkey crumbs (less preferred food) consumed less of the turkey crumbs, and showed elevated activity and exploratory feeder probing with respect to unshifted starlings exposed throughout to turkey crumbs. This is the first report of consummatory SNC in birds. In experiment 2, two groups differed in the amount of information. Initially, both groups encountered simultaneously one hopper with mealworms and three with turkey crumbs. The mealworm hopper was colour coded in group ‘cued’ but not in group ‘uncued’. After a shift, all four feeders contained turkey crumbs and were signalled by the colour associated with turkey crumbs before the shift. The two groups did not differ in postshift consumption, and increased overall activity similarly after the shift. Exploratory feeder probing, however, increased significantly less in group cued than in group uncued, consistent with the view that informed animals adjusted faster (ceased searching for the preferred food) to the new conditions. The dissociation between exploration and consumption in their sensitivity to available information during the reward downshift is discussed in terms of the adaptive implications of SNC.